Penilaian Sejawat Berkelompok Sebagai Solusi Problematika Asesmen Keterampilan Berbicara - Sudarsri Lestari (LPPM Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2017)
This article aims to explain the problematic of the assessment of speaking skills. Many teachers find it difficult to do the assessment. In this study used observational studies and interviews of teachers to find out the real situation regarding the use of speaking assessment. It turns out that many problems are found in the use of speaking skill assessment in detail in this research. Through this study also offered peer group appraisal as an alternative solution for conducting speaking assessment.